An Ethnobotanical and Sociocultural Study of the Utilization of Katojo as a Strategic Food Resource by the Kayuadi Island Community of the Selayar Archipelago - Alin Liana; Andi Nur Samsi; Irnayanti Bahar (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2025)
Katojo (Tacca palmata Blume), a wild tuber species, is known to be carcinogenic. However, for the people of Kayuadi Island in the Selayar Archipelago, this plant is an important food source, especially during the dry season. This study examines the ethnobotanical knowledge and sociocultural values associated with katojo utilization and its implications for local food security. This study employs a qualitative research method that combines participatory observation, in-depth interviews, and documentation of traditional processing methods and specimen collection. The results demonstrate that the people of Kayuadi Island not only treat katojo as an alternative food source but also as a symbol of resilience and independence. Additionally, local knowledge plays an important role in mitigating toxicity risks through traditional detoxification techniques that enable the safe consumption of katojo during food emergencies. These findings confirm that local knowledge is a valuable asset for food diversification relevant to the national food security agenda. Optimizing the development of katojo as an alternative food source requires scientific validation of traditional processing methods, food safety standardization, and strengthening the capacity of local communities. This study also emphasizes protecting traditional knowledge and preserving local biodiversity as integral parts of long-term food security strategies. The study is expected to contribute to our understanding of the relationship between ecology, culture, and food security and to open opportunities for integrating ethnobotanical practices into more inclusive and sustainable food policies